2021
DOI: 10.1038/s41598-021-93324-3
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting drivers and trends of ocean acidification in the subarctic Atlantic

Abstract: The processes of warming, anthropogenic CO2 (Canth) accumulation, decreasing pHT (increasing [H+]T; concentration in total scale) and calcium carbonate saturation in the subarctic zone of the North Atlantic are unequivocal in the time-series measurements of the Iceland (IS-TS, 1985–2003) and Irminger Sea (IRM-TS, 1983–2013) stations. Both stations show high rates of Canth accumulation with different rates of warming, salinification and stratification linked to regional circulation and dynamics. At the IS-TS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
2
14
1
Order By: Relevance
“…To reduce these uncertainties, one needs long-term (20 years or more) sea surface observations of oceanic carbon parameters, as obtained for example in the North Atlantic (e.g. Leseurre et al, 2020;Pérez et al, 2021) or in the western North Pacific (e.g. Midorikawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce these uncertainties, one needs long-term (20 years or more) sea surface observations of oceanic carbon parameters, as obtained for example in the North Atlantic (e.g. Leseurre et al, 2020;Pérez et al, 2021) or in the western North Pacific (e.g. Midorikawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Surface waters are most susceptible to decreasing CaCO3 saturation states and pH values as a consequence of anthropogenic carbon from the atmosphere as documented by Eulerian time series measurements (Bates et al, 2014). However, ocean 1110 acidification signals are also already being observed in the ocean at deeper levels such as in the Iceland Sea (Ólafsson et al, 2009) and in the North Atlantic (Vázquez-Rodríguez et al, 2012;Pérez et al, 2021). In some areas of the Nordic Seas, a pH drop can be detected down to depths of 2000 m (Fransner et al, 2022).…”
Section: Lysocline/calcium Carbonate Compensation Depth Changesmentioning
confidence: 98%
“…For the overall Nordic Seas, the mean decrease in pH over the last four decades is slightly larger (0.0025 yr -1 ) than the global mean for surface water (ca. -0.0018 yr -1 or -0.0017 yr -1 , Lauvset et al (2015), Chau et al (2023), Pérez et al (2021), see also the reprocessed data product between 1985 and 2021, 1015 from Copernicus: https://data.marine.copernicus.eu/product/GLOBAL_OMI_HEALTH_carbon_ph_area_averaged/description; last accessed 06.07.2023). However, there are large regional differences, and the Norwegian Sea shows almost twice the annual pH decrease (0.0034 yr -1 ) compared to other time series stations (Fransner et al, 2022;Skjelvan et al, 2022) observed between 1994-2021 in the Norwegian Sea (Skjelvan et al, 2022) and off the Iberian Peninsula (Flecha et al, 2019;Fontela et al, 2020).…”
Section: North Atlantic and Nordic Seasmentioning
confidence: 99%
“…Carbon uptake, on the other hand, is primarily driven by the rate of increase in the atmospheric CO 2 levels, thus depends on the trajectory of anthropogenic carbon emission. A significant fraction of anthropogenic CO 2 emissions is absorbed by oceans, increasing the concentrations of dissolved inorganic carbon (DIC) and thus causing acidification (Perez et al, 2021;Jiang et al, 2023;Ma et al, 2023). The increase in DIC affects the ability of the ocean to continue absorbing CO 2 from the atmosphere, as the ocean becomes more saturated with CO 2 (Le Queŕéet al, 2007;Keppler et al, 2023).…”
Section: Introductionmentioning
confidence: 99%